(untitled) (Res Gesta, 2018)
This article addresses the position assumed by the Argentine Government to the conflict over the Chaco Boreal between Bolivia and Paraguay, and the role played by it in the negotiation process leading to avoid –at first- and put an end –then- to the war. For this, the successive instances of mediation - Neutral Commission, League of Nations, ABCP group- and the performance of Argentina in each of them are analyzed, in order to unravel how this finally achieved that the postwar terms were negotiated at the Buenos Aires Conference (1935-1938). The epistolary exchange between key actors, writings of the Minister of Foreign Affairs -Carlos Saavedra Lamas-, documents of the Foreign Affairs Archive and discussions in the Parliament are some of the main sources used, in search of new contributions to understand both the reasons and interests that were hidden behind one of the most important actions of the Argentine Government in terms of international policy, as well as its consequences and results for the country and the region.